DEVELOPMENT OF TECHNOLOGY AND ANALYSIS OF ANTIFOOD MULTICOMPONENT MEDICINAL FORMS, INCLUDING CONTAINING NANOPARTICLES - I. A. Samkova; O. A. Melnikova; A. Yu. Petrov (Разработка и регистрация лекарственных средств, 2019)
In this article, experimental-industrial regulations for multi-component dosage forms for external use, including those containing nanoparticles, are presented. These forms are developed on the basis of the pharmaceutical composition "Novocomb", which has antiseptic, local anesthetic and prolonging action. Our preference was given to the following forms: external solution, ointment and napkin for external use. Evaluation of the obtained dosage forms was carried out for such indicators as authenticity, chromaticity, pH, content of active substances. An evaluation of antimicrobial activity and pharmacological action was performed, on the basis of which the principle of action of the composition on the burn injury model is presented.